2022
DOI: 10.15316/sjafs.2022.060
|View full text |Cite
|
Sign up to set email alerts
|

Profitability Analysis of Catfish (Clarias gariepinus) Production in Edo State, Nigeria

Abstract: The continuous importation of fish portends a colossal loss of foreign exchange reserved to Nigeria which requires urgent attention to boost fish production. It is against this backdrop that this study analyzed the profitability analysis of catfish production in Edo State, Nigeria. It specifically describe the production characteristics of the catfish farmers, estimate the input and output quantities of catfish, determine the profitability and identify the constraints associated with catfish production in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 8 publications
4
12
0
Order By: Relevance
“…This result conforms to the findings of Amachree, Jamabo and Joseph, (2019) [4] , that majority of catfish farmers in Rivers State, South-south, Nigeria, used concrete pond. It also agreed with the report of Imade and Egbodon, (2021) [16] , that earthen pond was the least used by catfish farmers in Delta State, South-south, Nigeria.…”
Section: Socio-economic Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…This result conforms to the findings of Amachree, Jamabo and Joseph, (2019) [4] , that majority of catfish farmers in Rivers State, South-south, Nigeria, used concrete pond. It also agreed with the report of Imade and Egbodon, (2021) [16] , that earthen pond was the least used by catfish farmers in Delta State, South-south, Nigeria.…”
Section: Socio-economic Characteristicssupporting
confidence: 87%
“…This, according to them, was because of its cost-effectiveness in terms of design and management as well as the limited impact on the environment. The findings of Imade and Egbodon, (2021) [16] also toed the same line when they reported that the mean levels of technical efficiency (TE) of the farmers under the production systems in Delta State, South-south Nigeria, were earthen pond (0.77), concrete pond (0.76) and plastic/tarpaulin pond (0.73) respectively. This was also the case in terms of output as Abasiekong, Ogban, and Idiong, (2021) reported that there were significant differences (P<.01) among the mean output of fish per ponds from the three production systems, with earthen pond having the highest value, followed by concrete pond, and mobile pond in Cross river State, South-south Nigeria.…”
Section: Allocative Efficiency Distributionmentioning
confidence: 61%
“…Fish is a global source of protein for humans and is included in the diet of some animals (Imade and Ahmadu, 2022). The importance of fish as a source of protein and food to every person cannot be overemphasized in the world today (Ajiboye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Given its high nutritional value, fish is an essential component of the diet of high and low income earners in Nigeria. It contains amino acids, vitamins and minerals (Yaqoob and Fasakin, 2021), and it happens to be the cheapest source of protein available to man (Imade and Ogieva, 2022). Fish production is often viewed as one of the means of increasing food production in food deficient countries like Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation